Design of an Adiabatic Calorimeter for Cementitious Mixtures by Multi-Objective Optimization - Jhonatan A. Becerra-Duitama; Mauricio Mauledoux; Óscar F. Avilés (Advances in Technology Innovation, 2023)
This study aims to design an adiabatic calorimeter for cementitious mixtures using NSGA-II and the Pareto optimal solution set. In this multi-objective optimization, the controller effort and heating time are selected as objective functions. Likewise, the volume and the material to be heated were chosen as decision variables. The optimal solution was selected using Nash bargaining methods. After implementing the optimal solution, the Wilcoxon test was applied to statistically validate the developed work. The measurements performed were compared with other research and it was observed an improvement in the measurement of heat of hydration in cementitious mixtures. Also, it was noted a decrease in the error in the temperature measurement.